Hyperfine Paschen–Back regime of potassium D2 line observed by Doppler-free spectroscopy. (19th June 2018) - Sargsyan, A; Klinger, E; Tonoyan, A; Leroy, C; Sarkisyan, D
Abstract: Selective reflection of a laser radiation from an interface formed by a dielectric window and a potassium atomic vapour confined in a nano-cell with 350 nm gap thickness is implemented for the first time to study the atomic transitions of K D2 line in external magnetic fields. In moderate B -fields, there are 44 individual Zeeman transitions which reduce to two groups (one formed by σ +, the other one by σ − circularly-polarised light), each containing eight atomic transitions, as the magnetic field increases. Each of these groups contains one so-called 'guiding' transition whose particularities are to have a probability (intensity) as well as a frequency shift slope (in MHz G −1 ) that are constant in the whole range of 0–10 kG magnetic fields. In the case of π -polarised laser radiation, among eight transitions, two are forbidden at B  = 0, yet their probabilities undergo a giant modification under the influence of a magnetic field. We demonstrate that for B -fields > 165 G a complete hyperfine Paschen–Back regime is observed. Other peculiarities of K D2 line behaviour in magnetic field are also presented. We show a very good agreement between theoretical calculations and experiments. The recording of the hyperfine Paschen–Back regime of K D2 line with high spectral resolution is demonstrated for the first time.